The Effect of Adverse Drug Reactions (ADRs) of Anti-psychotics on the Quality of Life of Outpatients with Schizophrenia at Soerojo Hospital, Magelang, Indonesia - Hutama, Tifan Adji; Karuniawati, Hidayah; Pangestuti, Rayi Citra Ayu (Borobudur Pharmacy Review, 2026)
Mental disorders are serious conditions of the brain that manifest as abnormalities that affect a person's behavior and character. Schizophrenia is one type of mental disorder that is widely experienced by the community. The primary therapy for schizophrenia is anti-psychotics with routine and long-term medication, which leads to Adverse Drug Reactions (ADRs). ADRs that appear have the potential to affect the quality of life of schizophrenia patients. The purpose of this study was to determine the effect of ADRs on the quality of life of schizophrenia patients at Soerojo Hospital Magelang. The study used a cross-sectional design. The population in this study was patients diagnosed with schizophrenia with consecutive sampling. The instruments used were the Naranjo and WHOQOL-BREF questionnaires to assess the quality of life of schizophrenia patients. Data analysis was conducted univariately using frequency distributions and bivariately using the nonparametric Mann-Whitney test. During the study, 109 patients met the inclusion and exclusion criteria. The majority of patients were male (59.63%), aged 41-60 years (55.96%), had been on treatment for 4-10 years (75.23%), had a high school education (39.45%), were taking a combination of clozapine and risperidone (29.36%), ADRs (71.55%), and had a moderate quality of life (55.05%). The most common ADRs experienced by patients using first-generation anti-psychotics were tremor, nausea, dizziness, and excessive salivation, each occurring at 9.09%. Meanwhile, the most common ADR for second-generation anti-psychotics was drowsiness (34.03%). ADRs were not significantly related to the quality of life of schizophrenia patients (p = 0.941